High HDL-C and high LDL-C are risk factors of pterygium in a population-based cross-sectional study in Southern China: the Dongguan Eye Study - Liang Zhang; Min Zhang; Ying Cui; Lixin Zhang; Guanrong Zhang; Qingyang Liu; Haike Guo; Qianli Meng; Siwen Zang; Chun-Han Lo; Yanlei Chen; Jin Zeng (BMJ Open)
Objectives To investigate the relationship between serum lipids and pterygium in a large-scale rural population aged 40 years or older from Southern China.Study design The Dongguan Eye Study was a cross-sectional population-based study from September 2011 to February 2012.Setting The area was set in the rural area of Dongguan, Southern China.Participants Adult rural population aged 40 or older.Methods Participants underwent physical, haematological and ophthalmic examinations.Primary and secondary outcome measures The frequency and risk factors of pterygium.Results A total of 11 357 participants were eligible for inclusion and 8952 (78.8%) participants were enrolled for the systemic and ophthalmic examinations. The prevalence of pterygium was 17.3% after adjusting the sex and age distribution, 22.0% in participants with hypercholesterolaemia (total cholesterol ≥6.22 mmol/L (240 mg/dL)) and 21.8% in those with low-density lipoprotein-cholesterol (LDL-C) ≥4.14 mmol/L (160 mg/dL), respectively. After adjusting for multiple confounding factors, higher level of high-density lipoprotein-cholesterol (HDL-C) (OR: 1.23, 95% CI: 1.06 to 1.41) and LDL-C (OR: 1.13, 95% CI: 1.06 to 1.20) were positively associated with the risk of pterygium. The ORs for HDL-C or LDL-C with pterygium were significantly greater in participants aged 40–49 years than those aged 50 years or above (P for interaction <0.001). Furthermore, increased HDL-C showed greater association with pterygium in normal body mass index (BMI) group compared with overweight group (P for interaction=0.002).Conclusion Increased HDL-C and LDL-C are risk factors of pterygium, especially in people <50 years or those with normal BMI level. Strict control of HDL-C and LDL-C may be a new prevention method in reducing the risk of pterygium.